The power of innate: Behavioural attachment and neural activity in responses to natural and artificial objects in filial imprinting in chicks - Cherepov, A. B.; Tiunova, A. A.; Anokhin, K. V. (Frontiers in Physiology, 2022)
Newly hatched domestic chicks are known to orient preferentially towards naturalistic stimuli resembling a conspecific. Here we examined to what extent this behavioral preference can be transcended by an artificial imprinting stimulus in both short-term and long-term tests. We also compared the expression maps of the plasticity associated c-fos gene in the brains of chicks imprinted to naturalistic (rotating stuffed jungle fowl) and artificial (rotating illuminated red box) stimuli. During training, the approach activity of chicks to naturalistic object was always higher than to artificial one. However, the induction of c-fos mRNA was significantly higher in chicks imprinted to a box than to a fowl, especially in the intermediate medial mesopallium, hyperpallium apicale, arcopallium and hippocampus. Initially, in the short-term test (10 minutes after the end of training), chicks had a higher preference for a red box than for a stuffed fowl. But in the long-term test (24 hours after imprinting), the response to an artificial object decreased to the level of preference for a naturalistic one. Our results thus show that despite artificial object causes a stronger c-fos novelty response and higher behavioral attachment in the short term, this preference is less stable and fades away, being overtaken by a more stable innate predisposition to naturalistic social object.